Manajemen Pendanaan dalam Meningkatkan Mutu Pendidikan Madrasah - Oktariana, Oktariana; Muspawi, Mohammad; Rahman, K. A. (Jurnal Ilmiah Dikdaya, 2024)
Improving the quality of human resources is greatly influenced by the quality of education. There is a systematic mechanism for preserving knowledge and information in education. The quality of education often focuses on the quality of graduates, but without a quality educational process, high quality graduates (output) cannot be obtained. With the current development of the education industry, funding can be said to be quite a complex issue that needs to be considered by education providers. Because the basic problems of education will be related to educational staff problems, learning mechanism problems, infrastructure problems, sales problems and other aspects related to financial problems. The teaching and learning process will be hampered by the failure of educational institutions to provide funds. Obstacles in the teaching and learning process automatically cause people to lose trust in the institution. However, excessive funding does not guarantee better school management (Winarsih, 2016 ). This research uses a qualitative descriptive research method, which is a method that studies the current situation of human groups, objects, and conditions with a system of thought, or a series of events in the present. here were 6 informants/subjects for this research, including the head of the madrasa, the deputy head of the madrasa in the field of infrastructure, the deputy head of the madrasa in the field of curriculum, the deputy head of the madrasa in the field of student affairs, the deputy head of the madrasa in the field of public relations and the educational staff of MI Mahabbatullah Jambi City. The results of the research show that Madrasah Ibtidaiyah Mahabbatullah Jambi City does the following in managing education funds: (1) Planning and formulating policies consisting of data collection, data processing, and diagnosis, summarizing needs, budgeting the necessary resources and choosing objectives, (2) plan, (3) outline the plan, (4) implement the plan, and (5) then revise and plan the next strategy.